Ácaros como bioindicadores da qualidade do solo em áreas de expansão da cultura da soja no Rio Grande do Sul - Giovenardi, Andréa da Rocha (2023)
The land-use change from native vegetation to pasture and subsequent from pasture to crop production (e.g., soybean cultivation) is economically necessary. However, it can cause soil degradation at the same time. The demand for food increases the need for soybean agricultural expansion to places that do not have favorable conditions for soybean cultivation. One of the impacts facing land-use change is related to the abundance and diversity of edaphic organisms, particularly mites. In addition, the land use change can modify the soil’s organic carbon stocks. In this study, five regions with different ages of land-use change were evaluated to measure the relationships among land-use change, mites, and soil organic carbon. The land-uses such as i) Atlantic Forest (MA) – Atlantic Forest fragment in the I and II regions, ii) Native field (CN) – Pampa biome in the II, III, IV, and V regions, iii) Cultivated pasture (PC) – extensive pastureland, and iv) Soybean (SO) – soybean cultivated under the no-tillage system in all regions were measured. This study tested the hypotheses that mites are biological indicators of land-use change for soybean agricultural expansion and indicators of organic carbon adding to the soil. The sampling was done in the top-soil layer (i.e., 0-10 cm depth) and mites were extracted using a Berlese-Tullgren Funnel and identified to the trophic family level. In the samples, soil organic carbon content was measured. The ecological indexes such as ShannonWeaver diversity (H’), Margalef biodiversity and Pielou equability index were carried out. In addition, multivariate statistical analyses of clustering and principal components were performed. In the five regions, 18 taxa were identified. The number of families ranged from 3 to 12. The Sarcoptiformes was the mite group with the highest abundance (70.6%), followed by Mesostigmata (26.4%), and Prostigmata (2.96%). In general, the ecological indexes were better under MA. Without considering MA, Pielou’s equability was higher under SO with older historic land-use change. The agricultural expansion for soybean cultivation in different regions of Rio Grande do Sul state reduced the diversity of edaphic mites when compared to the native vegetation. The principal component analysis indicated stability in the older region where organisms were ordered by land use and physical and chemical attributes, while in the II and IV regions, organisms were ordered only by land use. Soil organic carbon stocks influenced the density of soil mites as well as the land-use change for soybean agricultural expansion altered soil carbon stock over time. Finally, sandy soils impacted the soil carbon and mites’ density.